2D PANORAMIC RADIOGRAPHY AND 3D CBCT OF MANDIBULAR CORTICAL LOSS IN SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) PATIENTS OF HASAN SADIKIN HOSPITAL: A CROSS SECTIONAL STUDY: RADIOGRAFI PANORAMIK 2D DAN CBCT 3D DARI HILANGNYA TULANG KORTIKAL MANDIBULAR DI SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) PADA PASIEN DI RUMAH SAKIT HASAN SADIKIN: STUDI CROSS SECTIONAL - Trelia Boel; Wilda H. Lubis; Ervina Sofyanti; Dewi Kartika; Wachjudi R Gunadi (TALENTA, 2017)
Systemic Lupus Erythematosus (SLE) is an autoimmune rheumatic disease that involves extensive inflammation of the bone regions. Studies showed that the long-term medication in SLE patientsaffects the quantity and quality of bones.This should be considered in any treatment administered, including dental treatment. This study was conducted to analyze mandibular cortical bone loss in SLE patients with 2D panoramic radiography and 3D Cone Beam Computerized Tomography (CBCT). The research was a cross-sectional study to measure 31 SLE Indonesian female outpatients in Internal Medicine Installationat Hasan Sadikin Hospital, Bandung in 2014. The mean age is 37.65±10.79 years with 5.23 ± 4.37 mg corticosteroid intake history for 2“20 years. There was a significant correlation in the mandibular cortical loss analyzed by 3D CBCT imaging based on corticosteroid dosage (p=0.026). In conclusion, the level of mandibular cortical bone loss observed by panoramic radiography was moderate while 3D CBCT imaging showed a severe level of loss in this study.